Aplikasi Keamanan Data Berbasis Web Menggunakan Algoritma AES 128 Untuk Enkripsi Dan Dekripsi Data - Aprizald, Aprizaldi; Hasan, Mhd Arief; Setiawan, Debi (JEKIN - Jurnal Teknik Informatika, 2022)
Folio Sheeter Division is a division of PT. Indah Kiat Pulp And Paper, which is located in Siak Regency, which is one of the leading paper mills in Riau Province. The Folio Sheeter Division requires an application that can process production data. The application can only be accessed internally, the production process is a company secret because in production there are several mix processes or mix formulations of quality and production quality so that the materials and data are not published. The process is digital text that is encrypted by user to user. Every production result, the supervisor will inform the assistant about the combination of the mix of production materials that will be processed to carry out production according to what consumers want. From the author's observations at the research site that the information shared by supervisors can be read by all employees or staff, this information can be seen clearly by users or staff who are not interested so that the production and process data can be known by other staff who are not interested, so it is possible that the data could be given to irresponsible parties. The types of data or files that exist are in the form of data records and supporting document files such as doc, xls and pdf. Production data will be encrypted with cryptographic techniques so that production data cannot be seen by others but the user himself or the user who is permitted in the form of decryption who can access it. Notification of information to staff or assistants is still fairly manual, because the provision of information in paper form and easily read by others. For this reason, the authors are interested in using the AES 128 algorithm to encrypt and decrypt data so that the process and production results in the form of data can be maintained.